USAHA MENINGKATKAN MANAJEMEN PEMBIAYAAN PENDIDIKAN OLEH KEPALA SEKOLAH (Studi Deskriptif kualitatif di SMKN 2 Bengkulu Tengah) - yusarman yusarman (UNIVERSITAS BENGKULU, 2022)
The objective of this reseach is to describe the effort to increase educational financing management by principal at Vocational Senior High School Number 2 Central of Bengkulu. The formulation of specific objectives are efforts to increase the planning, coordinating, actuating, controlling, and accounting educational financing management. The method used in this study was descriptive qualitatif. The data for this study were obtained from interview, observation, and documentation.The data analysis technique used in this study was desctiptive- qualitative.The result of this reseach shows that the efforts to increase educational financing management by headmaster at Vocational Senior High School number 2 Central of Bengkulu was implemented through planning, coordinating, actuating, controlling, and accounting.